A biocompatible Pd-based BMG with excellent corrosive-wear resistance for implant applications. (September 2020) - Hua, Nengbin; Hong, Xiaoshi; Liao, Zhenlong; Wang, Qianting; Zhang, Lei; Guo, Qiaohang; Ye, Xiaoyun; Brechtl, Jamieson; Liaw, Peter K.
Abstract: The mechanical properties, electrochemical behavior, wear and corrosive-wear performance of a Pd40 Cu30 Ni10 P20 bulk metallic glass (BMG) were studied. It is found that the Pd-based BMG shows high hardness of over 500 HV, which is superior to that of conventional biomedical alloys, like the CoCrMo alloy, 316 L stainless steel (SS), and Ti6Al4V alloy. The Pd-based BMG possesses a great corrosion resistance in the phosphate buffer saline (PBS) solution, which is ascribed to the formation of a highly-protective Pd-enriched sub-surface structure. The Pd-based BMG exhibits the greater dry- and corrosive-wear resistance than that of traditional crystalline biomedical alloys studied in this work. This trend can effectively ensure the working longevity of the Pd-based BMG as orthopedic implant. The triobocorrosion experiment results illustrate that the extremely high corrosive-wear resistance of the Pd-based BMG can be attributed to the high passivation capacity during wet sliding. The possible mechanism of the corrosion-accelerating wear deterioration is discussed, which provides the guidance for the improvement in the corrosive-wear resistance of Pd-based BMGs for their potential biomedical applications. Highlights: ThePd-basedBMGexhibitshighstrength, hardness, andlowYoung'smodulus. TheBMGhassuperiordry- andwet-wearresistancetocrystallinebiometals. TheBMGpossessesthebettercorrosionpropertythanthatof316LSS. ThePd-enrichedsub-surfacestructureofBMGoffersthegreatcorrosionbehavior. The passivation during sliding renders BMG the excellent corrosive-wear resistance.